Students' and lecturers' perception towards student-centred learning method: the 4-Pit Stop 6-Motion Technique / Maslinawati Mohammada, Intan Waheedah Othman, Raja Nurul Afiah Raja Abdullah, Hairul Suhaimi Nahard - Mohammad, Maslinawati; Othman, Intan Waheedah; Raja Abdullah, Raja Nurul Afiah; Nahar, Hairul Suhaimi (UiTM Press, 2020)
Prior research on culture suggests that people are culturally heterogeneous. The culture heterogeneity is based on the varying region, religion, gender, generation and class. The extant literature has established four cultural dimensions which differentiate national culture values into power distance, asculinity versus femininity, individualism versus collectivism, and uncertainty avoidance2. From the perspective of the Malaysian races, the first two value dimensions i.e. power distance and masculinity versus femininity and define Malay cultural values as feminine (such as discretion and modesty) and high power distance. These effectively create unique personality traits among the Malay students in the educational setting which are shyness and introversion, as well as relatively wide social gap between teachers and learners. Accordingly, this necessitates the conventional teaching method to be less effective for Malay learners as learning styles has been identified in the literature to be culturally driven. Against this theoretical conjecture, we develop an alternative, non-conventional teaching method termed the "4-pitstop and 6-motion technique" (4P6M) which aims at removing students' shyness by creating a relaxed learning nvironment whilst eliminating the power distance by letting students to teach their friends under the teacher's oversight.